Pengukuran Parameter Sistem PV Power Plant Tersambung Pada Jaringan Tenaga Listrik Berdasarkan Real Time Clock - Habib Satria (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2020)
The research describes the performance and accuracy of various interconnected sensors from the measurement results of photovoltaic energy conversion from power plants connected to the electricity grid from PLN. In data retrieval, PLX-DAQ software is used as a software for data loggers. The hardware used is a Pollycristallin type solar panel with a capacity of 2.08 kW, Arduino, and several sensor components that are used as hardware. In this developed tool, the component used to measure the temperature and surface of the panel is the DHT11 sensor, the component for measuring DC current is the ACS1712 sensor, the component for measuring DC voltage is the ZMPT101B sensor, and the component for measuring currents and voltages sourced from PLN electricity is sensor PZEM-004. Arduino will record data from these components, which is then interfaced to Excel Spreadsheet processing in the form of presenting data tables and graphics in real time. The DC voltage sensor calibration test has an average error of 0.63% and an AC voltage of 0.42%, while the DC current sensor has an average error of 2.21%, and the AC sensor current has an average error of 2.07% with all sensors in the normal reading limit category. The measurement results with the maximum electrical energy consumption capacity in the DC power measurement reached 1777.8 W, while for the maximum AC power capacity measurement it reached a value of 1834 W and occurred during peak loads at 12.00 PM.